Labour migration patterns in Europe : recent trends, future challenges - Guardia, Diez N.; Pichelmann, Karl.; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium: European Comission: Directorate-General for Economic and Financial Affairs, 2006)
In the last few years, issues related to international migration are receiving increasing attention from policy makers. This reflects mainly the changes in the magnitude and composition of migration flows. Net migration into the EU has risen again during the period 1998 to 2003. With an overall level of around 4 per thousand, relative immigration levels into the EU appear to be at present somewhat higher than those into the US (3.3 per thousand). High irregular migration, with estimates of the relation between regular and irregular immigration running between 1:0,3 and 1:1, and high numbers of asylum applicants indicate an increase in migration pressure during the last decade. Major changes in the source and destination of migrants have also taken place: traditional receiving countries have lost prominence while Southern European countries, who were sending countries until fairly recently, have become receiving countries, and some Eastern European Member States are now both sending and receiving migrants.
Economic Papers